Utilization of Biogas Liquid Waste For Starter In The Fermentation of Rice Husk As A Potential Feed For Poultry - Osfar Sjofjan; Danung Nur Adli; Irfan Djunaidi; Kuncoro Kuncoro (Faculty of Animal Science, Jenderal Soedirman University in associate with the Animal Scientist Society of Indonesia (ISPI) and the Indonesian Association of Nutrition and Feed Science (AINI), 2020)
The research was aimed to evaluate the effect of biogas liquid waste as a fermentation starter of rice husk to the nutrient content, gross energy and bulk density. The method used laboratory experiment using a completely randomized design (CRD) on factorial pattern (6 x 5) with the level of biogas waste liquid : P0-treatment (0% negative control), P0+ (Cellulomonas sp as positive control), P1 (5%), P2 (10%), P3 (15%), P4 (20%) ml/g, and the incubation time : T0 (0 day control ), T1(7 days), T2 (14 days), T3 (21 days) and T4 (28 days). The variables measured was the content of ash, crude protein, crude fiber, crude fat, gross energy and bulk density. Data were analyzed by analysis of variance (anova) CRD Factorial pattern and if there is a significant difference was followed by Duncan's Multiple Range Test. The results of research was the level of biogas liquid waste and the incubation time provides a significant influence (P<0.01) on the nutrient content, gross energy and bulk density of rice husk. The interaction level liquid waste provision of biogas and incubation time was highly significant (P<0.01) on the nutrient content, gross energy and bulk density. It can be concluded that the addition of biogas liquid waste 15% (ml/g) with a time of incubation for 21 days have best rice husk quality content based on improvement of crude protein, crude fat, and gross energy with lowest crude fiber.